Evaluating search results in exploratory search - Mahdi M.N.; Ahmad A.R.; Ismail R. (Science Publishing Corporation Inc, 2023)
The volume of information available on the World Wide Web is quite significant. This plethora of information has, to a large extent constantly challenged researchers in seeking for ways of making the information easily accessible to end users in as convenient ways as possible. Characteristically, ensuring the accessibility of this large amount of information involves three all-encompassing processes of retrieval, organization and presentation. The World Wide Web offers a platform for sharing information from large database repositories globally. However, information needs to be searched with specialized tools commonly referred to as search engines. While a number of search engines does presently exist, most of these search engines are noted for their inability to retrieve information usable to the end user. It is therefore critical for the results generated from search engines to be intelligently organized for the optimal usefulness of the information to the searcher. Exploratory web technologies is capable of filing this gap. Therefore, this paper reviews exploratory search as a mechanism for conducting result-oriented search. It also reviews the ways of evaluating the search results obtained from an exploratory search. 2018 Authors.